Analysis of sequence variations in the GABA gated chloride gene associated with resistance to fipronil in Rhipicephalus (Boophilus) microplus ticks from Argentina - Sarli, Macarena; Torrents, Jorgelina; Morel, Nicolas; Nava, Santiago (Elsevier, 2022)
This study aimed to evaluate the sequence variations of the GABA-Cl gene of Rhipicephalus (Boophilus) microplus ticks from Argentina with different resistance levels to fipronil. Genomic DNA was obtained from engorged females (n = 50) of fipronil-susceptible and resistant tick field populations from five localities in northern Argentina. Tick populations were tested for fipronil resistance by in vitro larval packet test. DNA encoding amino acid residues 264–360 of the GABA-Cl was amplified by PCR. PCR products were sequenced and the translated amino acid sequences were aligned and compared among each other and with sequences of the GABA-Cl belonging to the Brazilian and Uruguayan reference strains fipronil-susceptible (Mozo) and resistant (RFSan and Juarez). All the GABA-Cl amino acid sequences obtained from the R. microplus specimens from Argentina were identical, regardless of the fipronil resistance-susceptibility status of each population. Mutations present in GABA-Cl sequence of RFSan and Juarez strains were not present in any of the populations from Argentina analyzed. These results indicate the failure of this gene as a molecular marker of resistance to fipronil, at least in the R. microplus populations from northern Argentina.